“Nivel de depresión, ansiedad y estrés en estudiantes de Estomatología- UNT durante la pandemia Covid-19, 2020” - Roncal Córdova, Karen Gissella (2022)
The present observational- descriptive and cross-sectional research study was to identify the level of depression, anxiety and stress in 3rd, 4th, 5th and 6th year students of the Faculty of Stomatology of the National University of Trujillo during the COVID-19 pandemic, 2020.The sample consisted of a total of 84 students, 53 females (63%) and 31 males (37%), from the third to sixth academic year to whom the DASS-21 scale was applied, which presents three factors to evaluate the presence of depression, anxiety and stress. The responses were analyzed using the SPSS v.26 program and the Chi-square test of homogeneity was used to compare the levels of the variables of interest.The results show that depression was found to be moderate (25%), mild (10.7%), severe (9.5%), very severe (3.6%) and 51.2% of the participants did not present depression; as for anxiety, this was found to be moderate (16.7%), mild (16. 7%), severe (14.3%), very severe (15.5%) and 36.9% did not present anxiety and the stress factor was found in mild (19%), moderate (15.5%), severe (15.5%), very severe (4.8%) and 45.2% did not present stress; according to the quantification of the DASS-21 scale. It is concluded that the students of the Faculty of Stomatology from the third to the sixth year presented some level of depression, anxiety and stress during the Covid-19 pandemic; depression was more frequent in the 3rd year with moderate and severe predominance in 25% of the cases.